TREND ANALISIS PENINGKATAN JUMLAH KUNJUNGAN PASIEN DITINJAU DARI MARKETING MIX - Ratna Wardani (Jurnal Ilmu Kesehatan Masyarakat, 2017)
Increase in human populations and the state of the economy more advanced, impact public awareness of increasing health.This provides a result to increase in the number of visitors in hospital.The purpose of this research is to analyze increasing trend the number of patient visits in terms of marketing mix done Hospital HVA Toeloengredjo. This research using design descriptive with research analysis using time series with a moving average model arima.Observational research method, with the subject is officer medical record and marketing officer, as well as its object was data on the number of patient visits new and old patient.Testing model results got that model ARIMA( 1,1,0 ) is a model that could be used to perform a forecast or estimate.A prediction visitors keeps increasing, where a prediction the number of visits all patients on the moon 60th(december 2016) is 10746 visits, a prediction the number of visits new patients is 1660 visits, a prediction the number of patient visits long been 9290 visits . Keywords : Time series , Visits , ARIM